The effect of tax knowledge and taxpayer awareness on BUMDes taxpayer compliance - Nasution, Wafiq Khotimah; Purnamasari, Dian Indri (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
Knowing the influence of education level, tax knowledge and taxpayer awareness on BUMDes taxpayer compliance is the aim of this research. The population of this study were all BUMDes registered at the Village Government Office (PMK) in Sleman Regency and this study used a saturated sample.Saturated sample is a sampling technique when all members of the population are sampled, the total population in this study was 59 BUMDes registered at the Village Government Office (PMK) in Sleman Regency and the sample in this study were 57 respondents who filled out the questionnaire, there were 2 BUMDes that did not fill in on the grounds that BUMDes had just been formed and the type of business had not yet been developed. This research uses primary data in the form of a questionnaire distributed throughout BUMDes. Testing the hypothesis in this study used multiple linear regression analysis with the help of SPSS software. The results of this study indicate that the knowledge of taxation and awareness of taxpayers affects the compliance of BUMDes taxpayers in Sleman Regency